TUBING SYSTEM PERFORMANCE PROFILING OF DRY GAS WELLS USING NEWTON RAPHSON ITERATION METHOD - CHINEDU WILFRED OKOLOGUME; ROTIMI OMONUSI (Journal of Engineering Studies and Research)
This paper focusses on the use of Newton Raphson iteration in determining gas compressibility factor (z) while performing tubing system performance for dry gas wells through the development of a computer model (TBG_SPARK). However, tubing performance analysis performed on the case study (Well-A and Well-B) revealed that the production system of Well-B performed better – since its tubing size and wellhead pressure was lower than that of Well-A. Also, investigations made using modified data revealed that, lower tubing sizes and higher wellhead pressures yield higher gas rates. Conversely, reverse was the case when wellhead pressures were not varied.